Three new species of Calyptotheca (Bryozoa: Lanceoporidae) from the Great Barrier Reef, tropical Australia - Sebastian, Pascal; Cumming, Robyn L. (Zootaxa, 2016)
The cheilostome bryozoans Calyptotheca wulguru n. sp. and Calyptotheca tilbrooki n. sp. (Lanceoporidae) are described from inter-reefal, sediment-dominated habitats of the Great Barrier Reef, and Calyptotheca churro n. sp. was washed up on a Heron Island beach, with uncertain origin. Calyptotheca wulguru n. sp. and C. churro n. sp. belong to a subgroup of Calyptotheca species with numerous small, oval, marginal adventitious avicularia and suboral nodular thickening or umbones. The vicarious avicularia of C. tilbrooki n. sp. are elongate-oval, unlike those of other known Calyptotheca species, and C. tilbrooki n. sp. has more pronounced orificial dimorphism than in any other known Calyptotheca species. Calyptotheca churro n. sp. has the most pronounced suboral umbo of all known Calyptotheca species. This study increases the known Calyptotheca species of the Great Barrier Reef to ten, and of tropical Australia to 14.